2012
DOI: 10.2308/accr-50232
|View full text |Cite
|
Sign up to set email alerts
|

Reward System Design and Group Creativity: An Experimental Investigation

Abstract: In an environment where three-person groups develop a creative solution to an important problem, we examine whether the efficacy of either individual- or group-based creativity-contingent incentives depends on whether they take the piece-rate or tournament form. We predict and find that group (intergroup) tournament pay increases group cohesion and collaborative efforts, which ultimately lead to a more creative group solution, relative to group piece-rate pay. While individual (intragroup) tournament pay incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 49 publications
1
53
1
4
Order By: Relevance
“…In this situation, employees perceive the high performance required by the stretch targets as assimilated into their own values, which facilitates the autonomous motivation necessary for their creativity and establishes what behavioral economics labels an instance of the ''motivation crowding-in effect'' (Frey 1994). As such, these findings extend the management accounting literature on incentive systems in creativity-dependent settings (e.g., Kachelmeier and Williamson 2010;Chen, Williamson, and Zhou 2012;Grabner 2014).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this situation, employees perceive the high performance required by the stretch targets as assimilated into their own values, which facilitates the autonomous motivation necessary for their creativity and establishes what behavioral economics labels an instance of the ''motivation crowding-in effect'' (Frey 1994). As such, these findings extend the management accounting literature on incentive systems in creativity-dependent settings (e.g., Kachelmeier and Williamson 2010;Chen, Williamson, and Zhou 2012;Grabner 2014).…”
Section: Introductionsupporting
confidence: 68%
“…7 The literature on target setting suggests, as might be expected, that challenging, but likely achievable, targets are often optimal for motivational purposes (Stedry 1960;Merchant and Manzoni 1989). However, the literature is more controversial where the expected type of tasks relate to creativity and innovation (Chen et al 2012;De Dreu, Baas, and Nijstad 2012;Byron and Khazanchi 2015). Elevating organizational aspirations, extremely difficult targets can spark energy among employees and promote exploratory learning for an improved future (Thompson et al 1997;Kerr and Landauer 2004;Chen and Jones 2005).…”
Section: Interrelation Of Controlsmentioning
confidence: 99%
“…The oldest participant 37 The significant effect remains even in a multi-variate regression after controlling for performance incentive, training, and other demographic variables. 38 Although this appears to be in contrast with results of Chen, Williamson, and Zhou (2012) who found that women were more creative than men, Chen et al's (2012) study involved computer-mediated collaboration which men used to a lesser degree than women. My study does not require group collaboration, so gender differences are not expected to be significant.…”
Section: Participantscontrasting
confidence: 54%
“…Dentre os principais resultados dos estudos iniciais, observa-se que desempenho em tarefas criativas é superior na presença de contratos de incentivo relativamente ao pagamento de salário fixo; no entanto, quando esse contrato de incentivo é baseado em uma medida de criatividade, o desempenho em tarefas criativas é inferior do que quando o contrato de incentivo é baseado em produtividade (Kachelmeier et al, 2008;Kachelmeier & Williamson, 2010). Estudos posteriores ampliam essa perspectiva inicial ao examinar o papel de contratos de incentivo sobre criatividade em contexto de grupo (Chen et al, 2012) ou o papel de mecanismos adicionais de controle, tal como nível de dificuldade das metas (Webb et al, 2013) e se a meta é de input ou de output (Brüggen et al, 2018). Em estudo mais recente, Kachelmeier et al (2019) examinam efeitos de diferentes contratos de incentivo sobre criatividade considerando dois estágios no processo de criatividade, um primeiro de preparação criativa e um segundo de incubação em que os ganhos decorrentes da etapa inicial são realizados.…”
Section: Sistemas De Controle Gerencial E Criatividadeunclassified
“…Nesses estudos, criatividade é definida como produção de ideias originais que podem contribuir para inovação, adaptação e crescimento organizacional (Kachelmeier et al, 2008). Em termos operacionais, Williamson e seus coautores têm utilizado diferentes variações para capturar criatividade dos participantes, com destaque para desenho de rebus puzzles (Kachelmeier et al, 2008;Kachelmeier & Williamson, 2010;Kachelmeier, Wang & Williamson, 2019), uso criativo para uma casa abandonada no campus da universidade (Chen, Williamson & Zhou, 2012) e desenvolvimento e breve descrição de novas tarefas experimentais (Brüggen et al, 2018). Em geral, o desempenho de participantes em tarefas criativas é avaliado por 'especialistas' que são informados terem sido os participantes solicitados a criar algo novo, inovador e útil.…”
unclassified